THE INFLUENCE OF COLLABORATIVE AND LEARNING STRATEGIES STUDY MOTIVATION ON LEARNING OUTCOMES ISLAMIC RELIGIOUS EDUCATION FOR SCHOOL STUDENTS COUNTRY BASIC 065015 MEDAN TUNTUNGAN - Ananda, Rusydi; Rifai, Muhammad; Mar'i, Khozali (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
The objectives of this research were to find out: (1) the different effect between colaborrative and competitive instructional strategy toward Islamic Education achievement, (2) the difference of the Islamic Education achievement between  student with high learning motivation and low learning motivation, and (3)  the interaction between instructional  strategy and learning motivation toward Islamic Education achievement. The instrument used to measure the Islamic Education achievement was a multiple choice test. The instrument used to measure the students’ learning motivation was questionnaire.  The normality test used Liliefors and the homogeneity test was Fisher test and Bartlett test. The data analysis technique was Analysis of Variance with two-way at the level of significance a = 0,05 followed by Scheffe test.  The research findings were: (1) on average the students’ Islamic Education achievement taught with colaborrative instructional strategy was = 28.14 which was higher than the average the  students’ Islamic Education achievement taught with competitive instructional strategy, which was = 27.07 with F count = 35.08 > Ftable = 3.96,  (2) on average the student’ Islamic Education achievement with high learning motivatione was = 29.91, which was higher than the student’ Islamic Education achievement with low learning motivation was = 26.05 with F count = 4.28 > F table = 3.96, and (3) there was an interaction between instructional strategy and learning motivation toward Islamic Education achievement with F count =  9,94 > F table= 3.96.